Body condition for the Qamanirjuaq Caribou Herd, 1966-1968 -Dauphine data - Dauphine, T.C. (Polar Data Catalogue, 2015)
These data include quantitative measurements of caribou body size and body condition indicators, listed in Summary below. The caribou in this sample were collected by shooting, and measurements were taken post-mortem. Spatial data, i.e. latitude/longitude coordinates exist for the general locations of the collections. Canadian Wildlife Service project.